IMPLEMENTATION OF WEBIX DYNAMIC SCRIPTING FOR WEB-BASED FORM APP DEVELOPMENT AS AN ALTERNATIVE TO DATA-COLLECTING APPLICATIONS - Cahyo Nugroho; Yerymia Alfa Susetyo (Informatika, Universitas Jenderal Soedirman, 2022)
In the 4th Industrial revolution, science and technology became increasingly advanced and more evolved. Besides that, data also became a new commodity that can be used to accomplish various things. One of the Indonesian retail companies that used data to improve the quality of the product is PT. XYZ. The oracle form is an application of form that used by PT XYZ for data collection. But the oracle form can no longer complied the company's needs, so the company needs an alternative form application that can be used to replace the oracle form. Therefore, a web-based form application was created and combined with dynamic scripting. Dynamic scripting was a proggraming technique to avoid writing the same code repeatedly. In this study, dynamic scripting's application was combined with the webix framework, resulting in a new framework that can shorten the code line and increase the time efficiency of the building of the form application.